Web-based tool compilation of analytical equations for groundwater management applications. (October 2018) - Glass, Jana; Jain, Ramandeep; Junghanns, Ralf; Sallwey, Jana; Fichtner, Thomas; Stefan, Catalin
Abstract: The INOWAS platform provides a compilation of free web-based tools for groundwater management. All tools are running on a web server and can be accessed via standard web browsers. The implemented analytical equations enable the assessment of saltwater intrusion induced by pumping or sea level rise, the calculation of travel time through unconfined aquifers and the evaluation of pumping-induced river drawdown. The groundwater mounding calculator can be used to estimate the rise of groundwater levels underneath infiltration basins. To determine the contaminant concentration downgradient of a constant source, an analytical tool solving the advection-dispersion equation can be utilized. All tools are incorporated into a decision support environment. The user is provided with detailed online support that contains the theoretical background of the tools, possible applications and examples. Highlights: Compilation of open-source, web-based analytical tools for groundwater management. Decision support environment providing theoretical background, application examples. Easy accessibility through standard web browser.